HUBUNGAN DUKUNGAN PENGASUH TENTANG PERILAKU HIDUP BERSIH DAN SEHAT SANTRI DENGAN PENCEGAHAN SKABIESDI PONDOK PESANTREN DARUL DAKWAH - Dwi Wahyuningsih, Binarti (JURNAL KEPERAWATAN SEHAT, 2016)
Islamic boarding school is an education place for students to learn Islamic knowledge under the guidance of an Ustadz or Kyai. Students in Islamic boarding school is basically the same as students in public schools that should be developed, which should receive special training, especially for their health and their growth. Clean and healthy living, especially personal hygiene in Islamic boarding schools usually received less attention from the students. Staying with a group of people like in boarding schools are at risk of easily contracted various skin diseases, particularly diseases of scabies. The purpose of this study is to determine if there any relationship between caregiver support of students’ healthy living and prevention of scabies in Darul Dakwah Boarding School. The research method used is the correlation analytic design with cross sectional approach. The population of the research is 72 female students in Darul Dakwah Boarding School. Through purposive sampling techniques, found the inclusion and exclusion criteria obtained samples of 71 people. Data are collected using a caregiver support and prevention of scabies questionnaire that presented in tabular form. Spearmans-rho test shows that p (0.000) <α (0.05) and the correlation coefficient = 0.764, so that Ho refused. It means that there is a relationship between caregiver support in students’ healthy living and scabies prevention. Caregivers need to support to their students to behave clean and healthy both emotionally, awards, instrumental and informative, so that students can maintain their own health by understanding how to prevent scabies.Keywords: Caregiver support, healthy living, scabies prevention